Highly efficient and sensitive membrane-based concentration process allows quantification, surveillance, and sequencing of viruses in large volumes of wastewater - G El soufi; L Di Jorio; Z Gerber; N Cluzel; J Van Assche; D Delafoy; R Olaso; C Daviaud; T Loustau; C Schwartz; D Trebouet; O Hernalsteens; et al. (Water Research, 2024)

Colonization of Pacific islands by parasites of low dispersal ability: phylogeography of two monogenean species parasitizing butterflyfishes in the South Pacific Ocean - Laetitia Plaisance; Vincent Rousset; Serge Morand; D. Timothy J. Littlewood (Journal of Biogeography, 2008)
Aim To investigate the phylogeographical patterns of two poorly dispersing but widely distributed monogenean species, Haliotrema aurigae and Euryhaliotrematoides grandis , gill parasites of coral reef fishes from the family Chaetodontidae. Location South Pacific Ocean (SPO). Methods Sequence data from the mitochondrial cytochrome oxidase subunit I (COI) gene were obtained from samples from five localities of the SPO (Heron Island, Lizard Island, Moorea, Palau and Wallis) for the two parasite species. Phylogenetic and genetic diversity analyses were used to reconstruct phylogeographical patterns, and dates of cladogenetic events were estimated. Results Overall, 50 individuals of 17 Haliotrema aurigae and 33 of Euryhaliotrematoides grandis were sequenced from five localities of the SPO for COI mtDNA (798 bp). Our results revealed a deep phylogeographical structure in the species Euryhaliotrematoides grandis . The molecular divergence between individuals from Moorea and individuals from the remaining localities (7.7%) may be related to Pleistocene sea‐level fluctuations. In contrast, Haliotrema aurigae shows no phylogeographical patterns with the presence of most of the mitochondrial haplotypes in every locality sampled. Main conclusions Our study shows contrasting phylogeographical patterns of the two monogenean parasite species studied, despite many shared characteristics. Both parasites are found on the same host family, share the same geographical range and ecology, and are phylogenetically close. We propose two hypotheses that may help explain the diparity: the hypotheses involve differences in the evolutionary age of the parasite species and their dispersal capabilities. Additionally, the lack of phylogeographical structure in Haliotrema aurigae contrasts with its apparently restricted dispersion, which is likely to occur during the egg stage of the life cycle, inducing a passive dispersal mechanism in butterflyfish monogeneans.

Effects of BAPTA-AM, Forskolin, DSF and Z.VAD.fmk on PDT-induced apoptosis and m-THPC phototoxicity on B16 cells - S. Thibaut; L. Bourré; D. Hernot; N. Rousset; Y. Lajat; T. Patrice (Apoptosis, 2002)

Test of the RAPD-PCR method to evaluate the efficacy of augmentative biological control withOrius (Het., Anthocoridae) - S. Gozlan; P. Millot; A. Rousset; D. Fournier (BioControl, 1997)